2021
DOI: 10.1136/bmjsit-2021-000098
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus non-operative treatment for ER-stress unstable Weber-B unimalleolar fractures: a study protocol for a prospective randomized non-inferiority (Super-Fin) trial

Abstract: Roughly two-thirds of ankle fractures are unimalleolar injuries, the Weber B-type fibula fracture being by far the most common type. Depending on the trauma and the accompanying soft-tissue injury, these fractures are either stable or unstable. Current clinical practice guidelines recommend surgical treatment for unstable Weber B-type fibula fractures. An ongoing randomized, parallel group, non-inferiority trial comparing surgery and non-operative treatment for unstable Weber B-type ankle fractures with alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Consecutive patients with an isolated Weber B/SER-type lateral malleolar fracture and congruent ankle mortise (MCS <4 mm and ≤1 mm wider than the superior clear space) were initially enrolled for pragmatic randomized controlled trials (RCT). 28 , 29 All patients gave written informed consent. A total of 87 study participants were gathered in the previous study 16 of which 26 could not be included due to variety of reasons reported previously 16 ; five were omitted due to severe metal artifacts, three due to subpar quality of MR images, and two because T2 maps were not acquired.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consecutive patients with an isolated Weber B/SER-type lateral malleolar fracture and congruent ankle mortise (MCS <4 mm and ≤1 mm wider than the superior clear space) were initially enrolled for pragmatic randomized controlled trials (RCT). 28 , 29 All patients gave written informed consent. A total of 87 study participants were gathered in the previous study 16 of which 26 could not be included due to variety of reasons reported previously 16 ; five were omitted due to severe metal artifacts, three due to subpar quality of MR images, and two because T2 maps were not acquired.…”
Section: Methodsmentioning
confidence: 99%
“…The final study group contained 51 subjects (23 female and 28 male; mean age 45 years, standard deviation (SD) 18 years; age range 16 to 82 years). The study group was split into two RCTs 28 , 29 based on the external-rotation stress test: stable fractures ( n = 28; 12 female, 16 male; mean age 42 years, SD 18 years; mean BMI 26.7 kg/m 2 , SD 4.9 kg/m 2 ) and unstable fractures ( n = 23; 11 female, 12 male; mean age 48 years, SD 19 years; mean BMI 26.9 kg/m 2 , SD 4.2 kg/m 2 ). Demographics are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation